The Role of E-Commerce in Improving the Competitiveness of MSMEs in the Global Market: Opportunities and Challenges - Suarniki, Ni Nyoman; Masela, Mesak Yandri; Deccasari, Dwi Danesty (Nomico, 2025)
The rapid development of technology and information requires people to get to know and always be in touch with the internet. One of the new lifestyles born is shopping via the internet or often called e-commerce. The utilization of e-commerce is not only carried out by large companies, but also by micro, small and medium enterprises (MSMEs). This study was conducted to identify the utilization of e-commerce in order to improve the competitiveness of MSMEs. The results show that the use of e-commerce can increase MSME revenues, facilitate product introduction to consumers, and make it easier to get customers. In addition, e-commerce helps save promotion costs and increase transaction speed, which in turn can improve the competitiveness of MSMEs. This research also explores the role of e-commerce as a strategic tool to improve the competitiveness of MSMEs in the global market. Through e-commerce, MSMEs can expand their market reach, reduce operational costs, and improve interactions with customers through digital platforms. While offering a range of opportunities, e-commerce adoption also presents significant challenges, such as low technological literacy, infrastructure limitations, and cybersecurity risks. Using a qualitative approach, this study analyzes the opportunities and challenges faced by MSMEs in integrating e-commerce into their operations. The results confirm that successful e-commerce implementation requires technology investment, capacity building, and a supportive policy framework. E-commerce has transformative potential for MSMEs, but its effective utilization requires efforts to overcome existing barriers to ensure sustainable growth and global competitiveness.